Systems dynamic modeling on sustainable apples agriculture - Samudra, Ferdianto Budi; Sitorus, Santun RP; Santosa, Edi; Machfud, Machfud (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
History shows the long process of apple plants originating from subtropical regions adapting to Indonesia's tropical climate until its popularity is increasingly marginalized and replaced with other commodities, as evidenced by the decreasing land area, especially in Batu City. Indonesia. In developing and analyzing solutions based on the principles of sustainable development, an integrated and holistic approach is required. To understand problems and find solutions, we can use Systems dynamics. The purpose of this study is to obtain a policy scenario that encourages sustainable apple farming. Data is collected from the local government and BPS City or Province so that the selected variables follow the specific location. The system approach is used to identify needs, problem formulation, preparation of input-output diagrams, cause-effect diagrams and stock-flow diagrams. A series of scenarios is created and tested through simulation to understand the system's dynamic behavior better and obtain the desired output. The best scenario was chosen, namely by replanting 10% of old plant each year, using integrated agriculture with 3 female and 1 male brooders, reduction of land change with 50% success, Local economic development by integrating tourist ticket and hotels with 0,75 kg apple fruits also increasing health support for students